A Model of the Topology of the Bank-Firm Credit Network and Its Role as Channel of Contagion - Thomas Lux (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
This paper proposes a stochastic model of a bipartite credit network between banks and the non-bank corporate sector that encapsulates basic stylized facts found in comprehensive data sets for bank-firm loans for a number of countries. When performing computational experiments with this model, we find that it shows a pronounced non-linear behavior under shocks: The default of a single unit will mostly have practically no knock-on effects, but might lead to an almost full-scale collapse of the entire system in a certain number of cases. The dependency of the overall outcome on firm characteristics like size or number of loans seems fuzzy. Distinguishing between contagion due to interbank credit and due to joint exposures to counterparty risk via loans to firms, the later channel appears more important for contagious spread of defaults.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: D85; G21; D83; 330; credit network; contagion; interbank network